A Study of Road Traffic Orthopedic Injuries at Tertiary Health Care Centre of Central India: Haddon Matrix approach - Mishra, SK; Meena , A; Chaurasia , S; Srivastav , S; Trivedi, A (Journal of Indian Academy of Forensic Medicine, 2024)
Road accidents continue to remain the leading cause of deaths, disabilities and hospitalization in India, as it is home to the second largest road network in the world. This massive network serves as the nation's lifeline, transporting the majority of all goods within the country, and it is the preferred option for mobilizing the country's passenger traffic. A cross sectional study was conducted amongst ward admitted patients in the Department of Orthopedics for one year. The data was collected using a pre-designed and pilot-tested questionnaire by interviewing patients. Multi-variate logistic regression was used to find the co-relationship of various factors responsible for causing trauma. The study included 560 patients; almost 70% were young adult males. The factors causing trauma were over speeding (Odds Ratio-0.97, P
Keywords: Road traffic injuries; Orthopedic trauma; Haddon matrix